ANALISIS SUMBER DAYA PETUGAS DENGANPENEMUAN DINI PENYAKIT KUSTADI WILAYAH DINAS KESEHATAN KABUPATEN SIMALUNGUN TAHUN 2019 - nahampun, hamonangan (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
The government has made efforts to eradicate leprosy through patient discovery, treatment of patients with Multi Drug Treatment (MDT), but has not yet succeeded in touching the root of the problem optimally. The problems in leprosy are more due to social and economic problems which are closely related to disabilities due to the delay in finding leprosy sufferers, so that sufferers are often found when they experience leprosy reactions that are not handled properly. The leprosy reaction is one of the complications in efforts to reduce and make leprosy no longer a national problem. This research aims to determine the resources of medical officers with early detection of leprosy in Simalungun District Health Office in 2019. This research conducted in the working area of Simalungun District Health Office in February-April 2020. This study used a qualitative method with a case study approach. Informants for qualitative methods are 24 people. The results of the study shows that the knowledge of medical officers is still low, they do not understand what leprosy is, the medical officers are not yet skilled in the management of leprosy cases, they have not been able to diagnose leprosy so that the treatment is delayed so the results of disability prevention is not working. The support budget for the leprosy program in Simalungun District Health Office is also minimum, so training for increasing the capacity of medical officers is very limited.